Numerical study on the rock breaking mechanism of high-pressure water jet-assisted TBM digging technique based on 2D-DEM modelling - Jiang, Yalong; Zeng, Jianjun; Jing, Liujie; Xu, Changjie; Xiong, Fuyang (Frontiers in Earth Science, 2023)
In order to improve the digging efficiency of tunnel boring machine (TBM) in high-strength and highly abrasive formations, high-pressure water jet-assisted TBM rock breaking technology has been developed and applied in steps. In this study, rock breaking mechanism by the new technology is investigated based on two- dimensional particle flow code (PFC2D) modelling. The force chain field distribution law and crack extension evolution characteristics of three typical rock breaking models are studied, and the influence of precutting slits parameters on force chain field distribution, rock sample rupture pattern, and peak load are further analysed. The results show that: 1) The rock breaking processes of the three typical modelling types (i.e., complete cutting model, same trajectory cutting model, and different trajectory cutting model) are different. Among them, the different trajectory cutting model is more likely to produce tensile failure and effectively reduce the penetration depth required for rock breaking. 2) The percentages of tension cracks to the total cracks in the three typical modellings are 90.8%, 93.9%, and 89.8%, respectively, indicating that the above three models are dominated by tension damage in the mesoscopic view. 3) With the increase of the depth of the precutting slit, the depth of the stress concentration zone beneath the disc cutter increases, inducing the increase of the angle between the edge of the stress concentration zone and the upper surface of the rock sample. Meanwhile, the peak load decreases, hence the difficulty of the TBM disc cutter penetration is gradually reduced.